Application of Prototype Method In System Design Integrated Database to Support Training Food and Nutrition Field at SEAMEO RECFON - Dodi Suswandi; Ivan Hanfi; Muhammad Yusro (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study discusses the application of the prototype method in the design of an integrated database system to support training in the field of food and nutrition. The case study used in this research is SEAMEO RECFON Southeast Asian Ministers of Education Organization Regional Center for Food and Nutrition (SEAMEO RECFON), which is an inter-ministerial organization of education in Southeast Asia in the field of food and nutrition. The research carried out is adjusted to the business processes running at SEAMEO RECFON, as well as according to ongoing events with current conditions. Researchers used a descriptive method in this study. The selected development method is the prototype method. The application of the prototype method makes it easier to design research that aims to describe and explain objects based on existing conditions. In the prototype research method, there is a prototyping section which makes it easier for researchers to make the necessary designs. This study aims to produce an integrated database system design. Based on the research results, this system has been successfully designed as expected so that the prototype that has been made can be used as a basis for continuing work on the system to be made. The results of this design can be used as a blueprint or documentation for the organization with the hope that later it can be used as literature to develop a database system to support training in the field of food and nutrition and all future program activities.